Word cloud analysis for the urgency of the role of islamic schools headmaster in merdeka curriculum implementation - Mokh Fathoni; Syarifuddin (12 Waiheru, 2024)
The government will be hoping for Islamic schools to prepare themselves for the implementation of a Merdeka curriculum to improve the quality of education in Islamic Schools. However, until now, the implementation of the Merdeka curriculum for Islamic Schools in Ambon City has not been optimal. This research aims to describe the causes, obstacles, and solutions in the implementation of the Merdeka curriculum of the Islamic Schools in Ambon City. This study is qualitative research in the form of a review of journal articles from the Google Scholar website. The number of journal articles found was 100, then 30 with the keyword "The role of headmaster in implementation of the Merdeka curriculum". The data obtained was in data form of the secondary then analyzed descriptively in table frequency and histogram graphs and then compared with the analysis using word clouds. The research results were that 21 journal articles concluded that the Islamic Schools were the key headmaster for implementing the Merdeka curriculum (70%), 4 journal articles concluded that responsibility was on the headmaster with the teacher for implementing the Merdeka curriculum (13.33%), and only one journal article concluded that the responsibility was on the headmaster with supervisors and teachers (3.33%). The obstacle experienced by the headmasters is that they do not yet understand the Merdeka curriculum well. The solutions found in this research are implementing socialization, workshops, clinical supervision, forming a learning committee or TEAM, mentoring, monitoring, reflection, and evaluations and follow-ups.